A phylogenetic study of two recently described endemic species of the Saxifraga granulata group from the central-north Mediterranean region (Italy) and their position in the context of the series Saxifraga (Saxifragaceae). Issue 8 (17th November 2018) - Coppi, Andrea; Lastrucci, Lorenzo; Ferretti, Giulio; Viciani, Daniele
Abstract : On two small islands of the Tuscan Archipelago, two new endemic species of the Saxifraga granulata group, namely S. caprariae and S. montis-christi, were recently described on a morphological basis. This led us to investigate these species using a molecular approach involving the analysis of ITS and trnL-F regions. Our aims were: to highlight their phylogenetic traits; to confirm or reject the hypothesis that they are more closely related to S. corsica than to S. granulata ; and to verify their phylogenetic position in the context of Saxifraga L. ser. Saxifraga . We considered all the species belonging to the ser. Saxifraga and some other species of sect. Saxifraga – a total of 19 species. We generated 10 new DNA sequences, six for ITS and four for trnL-trnF. We produced separate Bayesian and Maximum likelihood trees for both ITS and trnL-trnF regions and we analysed the genetic distances among the new endemics and the more closely related species. The phylogenetic analyses showed that S. caprariae and S. montis-christi are relatively well separated from S. granulata and more related to S. corsica . This supports the taxonomic treatment previously proposed. We showed that the results of our phylogenetic analysis are in agreement with our biogeographic knowledge of the Tuscan Archipelago and the neighbouring territories and emphasize the conservation relevance of these findings.